Feaella (Tetrafeaella) obscura sp. nov. – a new pseudoscorpion species from the Maldives (Arachnida, Pseudoscorpiones), and an updated identification key to the subgenus Feaella (Tetrafeaella) - János Novák; Michelle Lorenz; Danilo Harms (Zoosystematics and Evolution, 2020)
The Feaellidae Ellingsen, 1906 is a small but ancient family of pseudoscorpions with 20 extant species across the Southern Hemisphere, and fossils from the Lower Cretaceous of Myanmar and the Eocoene of Europe. Here, we describe and illustrate Feaella (Tetrafeaella) obscura sp. nov. as a new species from the Maldives archipelago in the Indian Ocean. This is the first record of Feaella from a young oceanic island and may indicate a potential for long-distance dispersal in this lineage. We also elevate Feaella (T.) capensis nana Beier, 1966 to full species rank as F. (T.) nana Beier, 1966 and provide an identification key to the members of the subgenus Feaella (Tetrafeaella), thereby facilitating the identification of species.